Prevalence of Germline Pathogenic and Likely Pathogenic Variants in Patients With Second Breast Cancers. Issue 6 (26th October 2020) - Yao K, Katharine A; Clifford, Jacob; Li, Shuwei; LaDuca, Holly; Hulick, Peter; Gutierrez, Stephanie; Black, Mary Helen
Abstract: Background: Few studies have examined gene-specific associations with contralateral and/or second breast cancer (SBC). Methods: The frequency of pathogenic and likely pathogenic (P/LP) variants in clinically actionable genes ( BRCA1, BRCA2, PTEN, TP53, CHEK2, CDH1, ATM, PALB2, NBN, and NF1 ) was compared between women with a primary breast cancer (PBC) and SBC who underwent multigene panel testing at a single diagnostic testing laboratory. Race- and ethnicity-specific logistic regression burden tests adjusted for age at diagnosis of first breast cancer, histology, presence of first- or second-degree relatives with breast cancer, and prior testing for BRCA1/2 genes were used to test for associations with SBC. All statistical tests were 2-sided. Results: The study was comprised of 75 550 women with PBC and 7728 with SBC. Median time between breast cancers for SBC was 11 (interquartile range = 6–17) years. Restricting to women tested for all actionable genes (n = 60 310), there were 4231 (7.8%) carriers of P/LP variants in actionable genes among the controls (PBC) compared with 652 (11.1%) women with SBC ( P < .001). Among Caucasians, exclusive of Ashkenazi Jewish women, those carrying a P/LP variant in a clinically actionable gene were 1.44 (95% confidence interval [CI] = 1.30 to 1.60) times as likely to have SBC than noncarriers, after accounting for potential confounders. Among African American and Hispanic women, a P/LP variant in a clinically actionable gene was 1.88 (95% CI = 1.36 to 2.56) and 1.66 (9% CI = 1.02 to 2.58) times as likely to be associated with SBC, respectively ( P < .001 and P = .03). Conclusion: Women with P/LP variants in breast cancer predisposition genes are more likely to have SBC than noncarriers. Prospective studies are needed confirm these findings.